Nigeria-Japan Economic Relations, 1999–2023 - Boge, Faruq Idowu; Olawoyin, Hawah Oluwaseun (Journal of Contemporary International Relations and Diplomacy, 2026)
Throughout modern international relations, partnerships between industrialized and developing countries often reflect deep structural imbalances in trade, investment, and cooperation. This pattern is evident in the economic relationship between Nigeria and Japan since the return of democratic governance in Nigeria in 1999. Despite stable diplomatic ties, official visits, and longstanding development assistance, economic interactions between the two countries have remained limited in scope and impact. This study examines the developments in the Nigeria-Japan economic relations between 1999 and 2023, with particular attention to trade, investment, and development aids. Employing a historical approach to data collation and interpretation; and subjecting them to analyses under the realist, liberalist, comparative cost advantage, and the dependency theories, the study identifies the factors that have contributed to the stagnant nature of the partnership. These include Japan’s cautious investment policy in sub-Saharan Africa and Nigeria’s internal economic and institutional challenges. Anchoring on the positions from dependency theory, the study argues that without significant adjustments on both sides, particularly in addressing structural limitations, the relationship will continue to fall short of its potential. It recommends greater policy clarity, economic reform, and mutual strategic alignment to enhance future cooperation.